Study on Pelvic Floor Dyssynergia and It’s Relevance to the Anorectal Bowel Dysfunctions and Management Guidelines - Inder Perkash (Issues and Developments in Medicine and Medical Research Vol. 2, 2022)
This chapter aims to highlights Pelvic Floor Dyssynergia (PFD) and It’s Relevance to the Anorectal Bowel Dysfunctions and Management Guidelines. Clinical presentation of PFD is straining at stools and feelings of incomplete evacuation. The need for perineal or vaginal pressure with relaxed pelvic floor to allow evacuation of stools is a strong clue for its diagnosis. Anorectal Manometry is now widely used to define bowel evacuation problems related to chronic constipation. In majority of the patients, an approach to the bowel program for adequate evacuation is individualized with a set time, diet control, and digital stimulation with and without a glycerin suppository; Often more than one procedure is necessary for individuals that have difficulty in developing an effective bowel routine.